Characteristic interactivity of landiolol, an ultra-short-acting highly selective β1-blocker, with biomimetic membranes: Comparisons with β1-selective esmolol and non-selective propranolol and alprenolol - Tsuchiya, Hironori; Mizogami, Maki (Frontiers in Pharmacology, 2013)
Although β1-blockers have been perioperatively used to reduce the cardiac disorders associated with general anesthesia, little is known about the mechanistic characteristics of ultra-short-acting highly selective β1-blocker landiolol. We studied its membrane-interacting property in comparison with other selective and nonselective β1-blockers. Biomimetic membranes prepared with phospholipids and cholesterol of varying compositions were treated with β1-selective landiolol and esmolol and nonselective propranolol and alprenolol at 0.5–200 µM. The membrane interactivity and the antioxidant activity were determined by measuring fluorescence polarization and by peroxidizing membrane lipids with peroxynitrite, respectively. Nonselective β1-blockers, but not selective ones, intensively acted on 1,2-dipalmitoylphosphatidylcholine liposomal membranes and cardiomyocyte-mimetic membranes to increase the membrane fluidity. Landiolol and its inactive metabolite distinctively decreased the fluidity of 1,2-dipalmitoylphosphatidylcholine liposomal membranes, suggesting that a membrane-rigidifying effect is attributed to the morpholine moiety in landiolol structure but unlikely to clinically contribute to the β1-blocking effect of landiolol. Propranolol and alprenolol interacted with lipid raft model membranes, whereas neither landiolol nor esmolol. All drugs fluidized mitochondria-mimetic membranes and inhibited the membrane lipid peroxidation with the potency correlating to their membrane interactivity. Landiolol is characterized as a drug devoid of the interactivity with membrane lipid rafts relating to β2-adrenergic receptor blockade. The differentiation between β1-blocking selectivity and nonselectivity is compatible with that between membrane noninteractivity and interactivity. The mitochondrial membrane fluidization by landiolol independent of blocking β1-adrenergic receptors is responsible for the antioxidant cardioprotection common to nonselective and selective β1-blockers.